A technology‐based information and coaching/support program and self‐efficacy of Asian American breast cancer survivors. Issue 1 (30th July 2020) - Im, Eun‐Ok; Yi, Jee‐Seon; Kim, Hyeoneui; Chee, Wonshik
Abstract: Women's self‐efficacy for coping with breast cancer is one of the key factors that lead to successful breast cancer survivorship. Due to the cultural stigma linked to breast cancer (e.g., breast cancer is a genetic disease), Asian Americans are known as a high‐risk group within breast cancer survivors. However, healthcare providers are challenged to promote women's self‐efficacy while considering their cultural beliefs and attitudes. In this study, the efficacy of a technology‐based information and coaching/support program was examined in improving self‐efficacy for coping with breast cancer among Asian American survivors. A randomized repeated measures control group study was conducted with 67 Asian American breast cancer survivors. The questions on background characteristics, the Personal Resource Questionnaire, the Perceived Isolation Scale, the Supportive Care Needs Survey Short Form 34, and the Cancer Behavior Inventory were used. The data were analyzed using repeated measurement analyses, χ 2 tests, and decision tree analyses. There were significant increases in the self‐efficacy scores of both control and intervention groups over time ( p  = .017). However, the increase in the control group's self‐efficacy scores was only up to post 1 month, and there was a decrease in the scores by post 3 months. When the participants were divided into high and low‐change groups based on the changes in their self‐efficacy scores for 3 months, the intervention group had more participants who belonged to the high‐change group ( p  = .036). The technology‐based intervention was effective in improving self‐efficacy for coping with breast cancer among Asian American breast cancer survivors.